Decoding the Guidelines of Invasive Pulmonary Aspergillosis in Critical Care Setting: Imaging Perspective - Garg, Anisha; Bhalla, Ashu Seith; Naranje, Priyanka; Vyas, Surabhi; Garg, Mandeep (Indian Journal of Radiology and Imaging, 2023)
Invasive pulmonary aspergillosis (IPA) is a common, life-threatening opportunistic fungal infection seen in susceptible individuals especially those admitted in critical care units. Multiple guidelines have been promulgated for the diagnosis of IPA, some of which are all inclusive, while others cater to specific patient groups. Microbiology forms the crux of the majority of the diagnostic tests/criteria; however, results take a considerable amount of time. Radiology can play an important role by bridging the gap to reach at an early diagnosis. Thus, the role of a radiologist cannot be overemphasized to recognize the typical and atypical imaging manifestations of invasive aspergillosis and aid in the swift management of these cases. This review decodes the terminology and various diagnostic criteria for IPA relevant to imaging studies. Further, the differences in imaging manifestations of IPA in neutropenic and non-neutropenic patients are also discussed.
Keywords: invasive pulmonary aspergillosis; chest CT; fungal lung disease; aspergillosis; galactomannan